Impact of coffee ground on ammonia concentration - Lee, Seungju (Open Science Journal, 2021)
Farmers should wait one week after spreading the composts until the ammonium concentration decreases. If the base component is too high, the plants could not grow well. If the soil is too acidic, the plants also cannot grow well. This study will reveal the optimal ratio of compost and coffee ground, which are base and acid, respectively. First, I prepare nine different ratios of compost, coffee ground, and potting soil. Then, five kidney beans were grown on each of the pots. Since kidney beans are easy to grow and grow fast, experiments were done with the kidney beans. All the other variables, including humidity, temperature, and lighting, were regulated. By measuring the soil pH, and the height and area of the leaves, the coffee and compost ratio was quantified. Our results show that an optimal coffee ground, compost, and soil combination should be 30-40-30 percent by weight. Furthermore, this study improves the ease of managing farms using coffee grounds and prevents the waste of the excessive amount of coffee residues being dumped every day.